Perencanaan Perbaikan Kualitas Pelayanan di Institut Teknologi Garut - Hilmi Aulawi; Rina Kurniawati; Agi Ferdiansyah Sunarya (Institut Teknologi Garut, 2023)
The aim of this research is to create an overview of student satisfaction regarding the quality of service at the Garut Institute of Technology (ITG) and create an improvement plan for ITG in the process of providing services. This is done using the service quality method which aims to create a picture of student satisfaction and quality function deployment to create an improvement plan. To plan improvements, questionnaires were distributed to ITG students from the 2019 - 2023 class with a population of 1427 with a sample of 100 students using a proportionate stratified random sampling technique. The research results show that ITG still does not meet student expectations for the services provided. To meet student expectations for services, five service priorities were obtained for improvement with as many as seven technical responses from ITG. To improve service quality, this is done by identifying the needs for each existing service attribute.